Coaches’ Perceptions of the Reduction of Athletic Commitment for Division II Student-Athletes: Development and Validation of a Measure of Athletic/Academic Balance - Huml, Matt R.; Hambrick, Marion E.; Hums, Mary A. (Journal of Intercollegiate Sport, 2016)
Growing concerns exist regarding the amount of time student-athletes spend honing their athletic craft at the potential expense of their academic pursuits. Recently, the National Collegiate Athletic Association (NCAA) Division II Management Council approved the Life in the Balance (LITB) initiative to allow student-athletes more time for academics and other extracurricular activities beyond their sport(s). The purpose of this study was to develop a reliable and valid measurement scale assessing coaches’ perceptions of balancing athletics and academics for studentathletes. Results of this study indicated three factors comprise the Athletic Academic Balance Scale (AABS): (a) policy impact, (b) contest reductions, and (c) midyear break. The AABS represents a reliable and valid scale to measure policy effectiveness for balancing athletics and academics for student-athletes. The scale extends role theory into student-athlete literature and helps assess the perception of internal stakeholders regarding future NCAA policies.